Language-Enriched Exercise plus Socialization for Older Adults with Dementia: Translation to Rural Communities - La Rue, Asenath; Felten, Kristen; Duschene, Kathie; MacFarlane, Dana; Price, Susan; Zimmerman, Suanne; Hafez, Stephanie (Seminars in Speech and Language, 2013)
Interventions that stimulate and engage individuals with dementia physically, cognitively, and socially offer promise for improving health and well-being and for potentially slowing functional losses with disease progression. We describe a volunteer-based intervention that combines physical exercise, cognitive-linguistic stimulation, and social outings for older persons living with dementia in rural communities. One-year follow-up data, although clearly preliminary (n = 8), suggest stability in global cognition, mood, and aspects of physical fitness. Challenges to implementing dementia interventions in rural areas are discussed.
Keywords: Dementia; exercise; cognitive stimulation; socialization